Investigation of Natural Gas Adsorption For the Recovery of Zeolite Waste - Alimova Zebo Xamidullaevna; Makhamadjanov MakhamatIbrakhim Akhmatjanovich; Magdiev Karimulla Irgashevich; Niyazova Gulxayo Parpiena (Genius Journals, 2023)
The purpose of this work is to study the utilization of zeolite waste for use in the adsorption treatment of natural gases and their influence on adsorption-desorption characteristics in natural gas desulfurization processes for the purpose of their secondary use in desulfurization processes. A method has been developed to restore the original properties of zeolites based on the oxidation of air pollution products with oxygen at moderate temperatures. The quality of the recovered zeolites at the pilot plant was controlled by laboratory analysis of the degree of recovery and pilot tests of the adsorption – desorption characteristics of the recovered zeolite samples at the GPU “Shurtangaz”.
Keywords: adsorption; zeolite waste; desulfurization; natural gas